DEVELOPMENT OF ARDUINO BASED TEMPERATURE AND HEAT PRACTICUM TOOLS IN SENIOR HIGH SCHOOL - Sari, Anna Yunita; Hamdani, Dedy; Purwanto, Andik (Universitas Tanjungpura, 2023)
This study aims to develop an Arduino Uno-based temperature and heat practicum tool using the DS18B20 temperature sensor for senior high school (SMA). This study uses the Research and Development Method following the procedure for designing a practicum tool that applies the ADDIE model development stage with stages, namely analysis, design, development, implementation and evaluation. However, this research is limited to the development stage. The data collection techniques used in this study were : (1) media expert validation sheets and material expert validation sheets to determine the feasibility of practicum tools and guidebooks, (2) student perception sheets to find out students responses to practicum tools and guidebooks. The results of experimental data using temperature and heat practicum tools as learning media that were developed fulfill the valid requirements with an average validator by media experts for practicum tools of 96.64% with the very feasible category, while for guidebooks 90.59% with the very feasible category. The validator material is 95.80% in a very feasible category, while for guidebooks 95.81% is in a very feasible category. Students' perception of practicum tools is 91% with a very feasible category, while for guidebooks 95% with a very feasible category. I think the tools can be used for physics learning.